Prioritas Pengadaan Buku Berdasarkan Data Kerusakan dan Kehilangan Menggunakan Metode Simple Additive Weighting - Syahid Hakam Abdul Halim; Yuhandri Yunus; Sumijan (SEULANGA SYSTEM PUBLISHER, 2021)
Supplying book which is estimated each year can fulfill the availability and requirement of books. With supplying book that has been done, it can increase the students reading interest in teaching and learning process. The frequency of using book in learning cause the book will be damaged or lost. The aim of this research is to find out the priority of supplying book based on damaged and lost data so that it can be used as a reference to determine the main priority in supplying book. If this priority can be determined, it will give the effect towards madrasah as well for librarian. The effect for madrasah is to give information about priority supplying book at school’s library. For librarian, the effect could be concluded as consideration in making decision to supplying the book at school’s library. To analyze the research, the researcher used 40 broken and lost data. Which is the broken data was obtained from the librarian of MAN 2 Kota Padang Panjang. In this research, the researcher used the Simple Additive Weighting with PHP programming and MySql database. The main concept of Simple Additive Weighting method is to find out the total rating performance for each alternative. The experiment of broken and lost data is done based on the alternative book which is normalized by attribute criteria (benefit or cost). The broken and lost data criteria was consisted of 4 criteria, they are 1 book’s stock criteria, 2. Book’s sheets criteria, 3. Book’s cover criteria, and 4. Book’s code criteria. The result ranking towards Simple Additive Weighting method based on 40 experiment data was found that 3 alternative books was obtained as priority in supplying book, they are Akidah Akhlak XI, Al Quran Hadist XI, and Ushul Fikih XI, which the Akidah Akhlak XI is the main priority.